2014
DOI: 10.1371/journal.pone.0107663
|View full text |Cite
|
Sign up to set email alerts
|

Post-Discharge Mortality in Children with Severe Malnutrition and Pneumonia in Bangladesh

Abstract: BackgroundPost-discharge mortality among children with severe illness in resource-limited settings is under-recognized and there are limited data. We evaluated post-discharge mortality in a recently reported cohort of children with severe malnutrition and pneumonia, and identified characteristics associated with an increased risk of death.MethodsYoung children (<5 years of age) with severe malnutrition (WHO criteria) and radiographic pneumonia on admission to Dhaka Hospital of icddr,b over a 15-month period we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 24 publications
11
84
3
2
Order By: Relevance
“…Our findings are consistent with that of a smaller study focused on children admitted to an intermediate care unit at the icddr,b, where those with pneumonia coinfection were found to have a two times higher mortality rate than those without pneumonia. 2 More recently, we have shown that children admitted with severe malnutrition and pneumonia to our diarrheal hospital have a 9% in-hospital death rate, 12 with an additional 9% children dying within 3 months of hospital discharge, even after inpatient nutritional rehabilitation was given. All of these data underline the potentially severe consequences of respiratory and gastrointestinal coinfection.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are consistent with that of a smaller study focused on children admitted to an intermediate care unit at the icddr,b, where those with pneumonia coinfection were found to have a two times higher mortality rate than those without pneumonia. 2 More recently, we have shown that children admitted with severe malnutrition and pneumonia to our diarrheal hospital have a 9% in-hospital death rate, 12 with an additional 9% children dying within 3 months of hospital discharge, even after inpatient nutritional rehabilitation was given. All of these data underline the potentially severe consequences of respiratory and gastrointestinal coinfection.…”
Section: Discussionmentioning
confidence: 94%
“…Even in nutritional rehabilitation centers that follow WHO-established treatment protocols, in-hospital mortality remains high, ranging from 10% to 30% of all treated cases (2). Postdischarge mortality is also significant, with studies reporting mortality rates of 8.7% within 3 mo of discharge (3), or ≤18% of all treated cases dying within 1 y of discharge (4). Furthermore, even if the children survive, they suffer from long-term adverse effects, showing patterns of thrifty growth and functional deficits such as weak hand grip and impaired cardiovascular capacity (5).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of SAM treatment also includes the reduction of susceptibility to life‐threatening infections, restoration of a healthy body composition, and improvement in neurocognitive status (Ngari et al, a). However, children with SAM remain at risk of developing severe illness and/or infections after treatment of clinical complications and discharged from hospital (Berkley et al, ; Chisti et al, ; Kerac et al, ; Ngari et al, a). A study by Kerac et al () that followed 1,024 children 1 year post‐discharge reported 5% hospital readmissions but 42% deaths, whereas Khanum et al () reported 1.2% emergency hospital readmissions.…”
Section: Discussionmentioning
confidence: 99%